2021
DOI: 10.1139/apnm-2020-0641
|View full text |Cite
|
Sign up to set email alerts
|

Power loss is attenuated following a second bout of high-intensity eccentric contractions due to the repeated bout effect’s protection of rate of torque and velocity development

Abstract: High intensity unaccustomed eccentric contractions result in weakness and power loss due to fatigue and muscle damage. Through the repeated bout effect (RBE), adaptations occur, then damage and weakness are attenuated following a subsequent bout. However, it is unclear whether the RBE protects peak power output. We investigated the influence of the RBE on power production and estimated fatigue- and damage-induced neuromuscular impairments following repeated high-intensity eccentric contractions. Twelve healthy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 42 publications
2
3
0
Order By: Relevance
“…These findings are also concordant with previous observations that protective adaptations to EIMD are associated with a greater relative recruitment of oxidative motor-units and subsequent preservation of high velocity performance (Hinks et al, 2021;Hortobagyi et al, 1996;Hyldahl et al, 2017). In the current study, however, these adaptations were absent in CG.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These findings are also concordant with previous observations that protective adaptations to EIMD are associated with a greater relative recruitment of oxidative motor-units and subsequent preservation of high velocity performance (Hinks et al, 2021;Hortobagyi et al, 1996;Hyldahl et al, 2017). In the current study, however, these adaptations were absent in CG.…”
Section: Discussionsupporting
confidence: 93%
“…That these observations were made following the use of an effective placebo intervention, double‐blind design, and reported alongside a reduction in swelling following B1 strengthens the case for a physiologically mediated effect of CG, with the combined α value from all three isokinetic interactions equating to P < 3.95 × 10 −8 . These findings are also concordant with previous observations that protective adaptations to EIMD are associated with a greater relative recruitment of oxidative motor‐units and subsequent preservation of high velocity performance (Hinks et al., 2021 ; Hortobagyi et al., 1996 ; Hyldahl et al., 2017 ). In the current study, however, these adaptations were absent in CG.…”
Section: Discussionsupporting
confidence: 92%
“…By contrast, a bi-phasic response was observed for the ratio of 20/100 Hz force output in exercise-naïve individuals such that the ratio was reduced 1 day and 7 days after the first, but not the second bout of BFR exercise (Sieljacks et al, 2016). This observation coincided with reductions in markers of muscle damage, suggesting a repeated bout effect (Hinks et al, 2021;Sieljacks et al, 2016). An important caveat to these studies was that BFR exercise was performed to task failure, whereas comparisons were made to either volume matched free-flow exercise, wherein participants stopped at a submaximal number of repetitions done during BFR exercise (Wernbom et al, 2012) or a standardized 150 maximal eccentric muscle actions (Sieljacks et al, 2016).…”
Section: Highlightsmentioning
confidence: 85%
“…Cardiorespiratory fitness was not tracked in this study; however, similar MVC force outputs were observed at the first and last exercise intervention (786 ± 292 vs. 760 ± 260 N, P = 0.8), supporting limited changes in maximal strength. Second, the crossover design may have resulted in a repeated bout effect that could affect the interpretation of the data (Hinks et al., 2021 ; Sieljacks et al., 2016 ). However, the repeated bout effect is minimized after a third bout in individuals unaccustomed to exercise (Chen et al., 2009 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation